Prediction of the Ionospheric Response to the 14 December 2020 Total Solar Eclipse Using Supim-Inpe - Martinez-Ledesma, M (American Geophysical Union, 2020)
We present the first prediction of the ionospheric response to the 14 December 2020 solar eclipse using the SUPIM-INPE model. Simulations are made for all known ionosonde stations for which solar obscuration is significant. The found response is similar to that previously reported for other eclipses, but it also shows a modification of the equatorial fountain transport that will impact the low latitudes after the event. In addition to the large reduction of electron concentration along the totality path (similar to 4.5 TECu, similar to 22%), a significant electron and oxygen ion temperature cooling is observed (up to similar to 400 K) followed by lasting temperature increases. Changes of up to similar to 1.5 TECu (similar to 5%) are also expected at the conjugate hemisphere. These predictions may serve as a reference for eventual ionospheric measurements of multiple instruments and are leading to a better understanding of the ionospheric response to solar eclipses.